2005
DOI: 10.1139/y05-112
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the chloride channel CLC-K in human airway epithelial cells

Abstract: Airway submucosal gland function is severely disrupted in cystic fibrosis (CF), as a result of genetic mutation of the cystic fibrosis transmembrane conductance regulator (CFTR), an apical membrane Cl -channel. To identify other Cl -channel types that could potentially substitute for lost CFTR function in these cells, we investigated the functional and molecular expression of Cl -channels in Calu-3 cells, a human cell line model of the submucosal gland serous cell. Whole cell patch clamp recording from these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…For all of these, selective expression in kidney tissue had already been reported by other groups (Shuck et al, 1994;Thomson et al, 1995;Estevez et al, 2001;Enomoto et al, 2002;Thedieck et al, 2005;Nusing et al, 2005;Mummery et al, 2005;Price et al, 2006) and was further confirmed by our RNA profiling (Fig. 2a, Table 2).…”
Section: Expression Profiling Of Candidate Genes In Human Tissuessupporting
confidence: 90%
See 1 more Smart Citation
“…For all of these, selective expression in kidney tissue had already been reported by other groups (Shuck et al, 1994;Thomson et al, 1995;Estevez et al, 2001;Enomoto et al, 2002;Thedieck et al, 2005;Nusing et al, 2005;Mummery et al, 2005;Price et al, 2006) and was further confirmed by our RNA profiling (Fig. 2a, Table 2).…”
Section: Expression Profiling Of Candidate Genes In Human Tissuessupporting
confidence: 90%
“…To have a benchmark for judging this ratio, we also calculated the percentage of (Thedieck et al, 2005;Thomson et al, 1995) downreg. (Thedieck et al, 2005) (testis, duodenum) KCNJ1 kidney + 2/5 +++ (Nusing et al, 2005;Shuck et al, 1994) no data SLC22A12 kidney + 0/5 ++ (Enomoto et al, 2002;Price et al, 2006) no data BSND kidney + 3/5 ++ (Estevez et al, 2001;Mummery et al, 2005) ESTs within dbEST specific for the respective tissue type. This value was 1.7% for kidney, 2.3% for colon and 4.4% for liver, suggesting that none of these tissues is overrepresented in the database.…”
Section: Generation Of An Annotated List Of Tissue Specific Genes Formentioning
confidence: 99%
“…In combination with the lack of inhibition we found using relatively high concentrations of tamoxifen and DIDS, this result was initially surprising to us. However, given the plethora of Cl -channels expressed in Calu-3 cells (Mummery et al 2005;Duta et al 2006), none of which have been ascribed definitive physiologic roles, it is possible that there is a phloretin-sensitive, DIDS-insensitive, volume-activated Clconductance in Calu-3 cells. Alternatively, there is evidence that phloretin can inhibit a K + conductance in squid giant axon (Spires and Begenisich 1989).…”
Section: Figmentioning
confidence: 99%
“…Studies focusing on the role of Cl -channels involved in volume regulation in airway cells have reported that the RVD response is lost in CF, primarily thought to be caused by dysfunction of volume-sensitive K + channels (Vazquez et al 2001). However, airway epithelial cells do possess volume-sensitive Cl -channels, such as the outward rectifying chloride channel (ORCC) and members of the chloride channel family (ClC) (Mummery et al 2005), which may potentially play a role in the RVD process. Therefore, the purpose of the present study was to identify candidate ion channels involved in volume regulation in Calu-3 cells, given their widespread use as a model for the serous cell.…”
Section: Introductionmentioning
confidence: 99%
“…Lung tissue is inherently heterogeneous in its composition of epithelial and non-epithelial cells, and the ratio of cell types will vary by specimen. This problem can eventually be reduced by the combination of the determination of protein contents with quantitative immunoblot densitometry of an epithelial marker protein such as CLCN2 [21,22,26].…”
Section: Discussionmentioning
confidence: 99%